2014
DOI: 10.1002/hup.2387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antipsychotics on bone mineral density and prolactin levels in patients with schizophrenia: a 12-month prospective study

Abstract: Objective Effects of conventional and atypical antipsychotics on bone mineral density (BMD) and serum prolactin levels (PRL) were examined in patients with schizophrenia. Methods One hundred and sixty-three first-episode inpatients with schizophrenia were recruited, to whom one of three conventional antipsychotics (perphenazine, sulpiride, and chlorpromazine) or one of three atypical antipsychotics (clozapine, quetiapine, and aripiprazole) was prescribed for 12 months as appropriate. BMD and PRL were tested be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…After removal of any duplicate articles, 3447 titles and abstracts were screened, of which 76 were assessed at full-text level for suitability for inclusion. Of these, ten met the necessary criteria for inclusion in the meta-analysis [21–23, 3541]. Two studies did not provide the full details of BMD measurements [42, 43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of any duplicate articles, 3447 titles and abstracts were screened, of which 76 were assessed at full-text level for suitability for inclusion. Of these, ten met the necessary criteria for inclusion in the meta-analysis [21–23, 3541]. Two studies did not provide the full details of BMD measurements [42, 43].…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of the control group was 34.7 years (SD = 9.1 years) and 58.7 % were female. Seven studies were conducted in Europe [21–23, 36, 37, 40, 41], and three in Asia [35, 38, 39]. Sample sizes ranged from 14 [37] to 229 [38].…”
Section: Resultsmentioning
confidence: 99%
“…It is not clear, however, if the drug-associated increase in falls is the sole cause of increased fractures, or if other mechanisms are also at play. Specifically, a number of recent cross-sectional and longitudinal clinical studies have found that AA use is associated with reduced BMD and increased fracture risk in both men and women [15][16][17][18] . Serum concentrations of a bone turnover marker, β-CrossLaps, were higher in patients treated with AA (n=31 drug-naïve first episode patients and n=85 AA monotherapy for 6 months) vs. drug-naive first-episode patients and normal subjects 19 .…”
Section: Psychiatric Medications and Bone: Clinical Evidencementioning
confidence: 99%
“…Serum concentrations of a bone turnover marker, β-CrossLaps, were higher in patients treated with AA (n=31 drug-naïve first episode patients and n=85 AA monotherapy for 6 months) vs. drug-naive first-episode patients and normal subjects 19 . A prospective study found that BMD in 120 firstepisode inpatients with schizophrenia prescribed either clozapine, quetiapine or aripiprazole was significantly lower than in matched healthy controls (n=90), 12-months after drug initiation 17 . In pediatric patients, AA-associated fractures were increased 2-3 fold with an associated reduction in bone mass [20][21] .…”
Section: Psychiatric Medications and Bone: Clinical Evidencementioning
confidence: 99%
“…3 Mechanisms that could help explain the relationship between hip fractures and antipsychotic use include prolactin elevation, extrapyramidal symptoms, sedative effects, and postural hypotension. Long-term exposure to prolactinelevating antipsychotics leads to reduced bone mineral density (BMD), 6,7 and markers of bone reabsorption correlate with prolactin elevation, while discontinuation of antipsychotics can cause improvement in markers of bone resorption. 8 Hip fractures are more common with antipsychotics that elevate prolactin than prolactin-sparing antipsychotics.…”
mentioning
confidence: 99%